Alacağın devri ve diğer hukuki kurumlarla karşılaştırılması - Bağce, Duygu (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Özel Hukuk Anabilim Dalı / Özel Hukuk Bilim Dalı, 2015)
Çalışmamızın temelini alacağın devri kurumu oluşturmaktadır. Alacağı devralmak isteyen alacaklı ile alacak hakkı sahibi arasında, borçlunun iradesi dışında gerçekleşen devir işlemi, üç taraflı bir hukuki ilişkidir. Bu ilişkideki tarafların hakları, borçları, karşılaşabilecekleri sorunlar çalışmamızda özel olarak ele alınmıştır. Alacağın devrinin uygulamada sıklıkla karşılaşılan bir müessese oluşu çalışmamızın hazırlanmasının başlıca nedenidir. Alacağın devrinin dışında birçok hukuki kurum ekonomik açıdan kişilerin hayatını kolaylaştırıcı rol oynar. Bu kurumlar birbirine benzediği kadar, farklılıklar da içermektedir. Alacağın devri ile diğer hukuki kurumlar arasındaki benzerlik ve farklılıklara dikkat çekilerek yapılacak olan bu karşılaştırmanın faydalı olacağı kanaatindeyiz. Çalışmamızda bahsi geçen konular, Türk Borçlar Kanunu ve Eski Borçlar Kanunumuzdaki düzenlemeler doğrultusunda karşılaştırmalı olarak yer almaktadır. Bununla birlikte çalışmamız; doktrin, içtihat ve günümüz uygulamaları esas alınarak oluşturulmuştur.
Transfer of receivable and comparison with the other legal organizations
The foundation of our study is constituted by organization of transfer of the receivable. The transfer transaction which is realized out of the will of the debtor, between the creditor who wants to takeover the receivable and the receivable right owner, is a three-party legal relationship. In this relationship, the rights of the parties, their obligations and the problems which may be encountered are taken up specially in our study properly. The fact that the transfer of the receivable is a frequently encountered establishment in practice is the primary reason of the preparation of our study. Apart from the transfer of the receivable, a lot of legal organizations play a facilitation role in the lives of the persons economically. As these organizations are similar to each others, they contain some differences as well. We are in an opinion that this comparison which shall be made and performed by means of attracting attention to the similarities and differences between the other legal organizations with the transfer of the receivable shall be quite beneficial and useful. The subjects which are mentioned in our study are taken up comparatively in accordance with the arrangements and regulations which are specified and stated in the Turkish Code of Obligations and the Former Law of Obligations. In addition to this, our study is formed by means of taking the doctrines, considerations and the applications of the day as basis.
Keywords: Hukuk; Law